A Cognitive Semantics Analysis of the Directional Motion Verbs wang往 and lai 来in the YiChing - Yang, Yancheng; Sinha, Chris (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The Chinese directional motion verbs wang往 and lai来can be glossed in English as ‘go’ and ‘come’, and the distinction between ‘go’ and ‘come’ in English is comparable to that between wang and lai in Chinese. Their usage in the YiChing is described and analyzed in this article. In the YiChing, wang and lai frequently co-occur in the same sentence, as well as occurring singly elsewhere. Based on a corpus analysis of the YiChing, combined with qualitative interpretive analysis, this article proposes that the majority of co-occurring usages of wang and lai are metaphorical. Metaphorical uses can also be found in the single usages of the two verbs. These metaphors are informed by the cultural practices and values that form the context for the YiChing as a cultural artifact as well as a classical text. Further, these directional motion verbs are based on metaphorical extensions that lead to their semantic changes (metaphors are based on the motion). Thus, the article further analyzes the role of metaphor and cultural context in the semantic changes to the directional motion verbs wang and lai.
Keywords: Wang 往 and lai 来; semantic change; deixis; metaphor; the YiChing